Career success across the globe: Insights from the 5C project - Mayrhofer, Wolfgang; Briscoe, Jon P.; Hall, Douglas Tim; Dickmann, Michael; Dries, Nicky; Dysvik, Anders; Kaše, Robert; Parry, Emma; Unite, Julie (Elsevier, 2016)
The Cross-Cultural Collaboration on Contemporary Careers (5C Project) conducted in-depth, longitudinal qualitative research into what career success means to people in a diverse range of countries; specifically: Australia, Austria, Belgium, Brazil, Canada, China, Colombia, Costa Rica, Finland, France, Germany, Greece, India, Israel, Italy, Japan, Korea, Malaysia, Mexico, Netherlands, Nigeria, Norway, Philippines, Portugal, Russian Federation, Serbia, Slovakia, Slovenia, South Africa, Spain, Thailand, Turkey, UK, and USA. This paper presents the seven major meanings of career success that emerged across these diverse global cultures and thus may be deemed relevant all around the world. These are financial security (being able to consistently provide the basic necessities for living), financial achievement (steadily making more money, wealth, incentives, and perks), learning and development (via continuous informal learning on the job and/or formal training and education), work-life-balance (between work and non-work, relationships, activities and interests), positive relationships (as signified by, for instance, enjoying working with people who you respect and admire), positive impact (by helping others in one’s immediate social environment and/or leaving some sort of legacy to a community, or society more broadly), and entrepreneurship founding one’s own enterprise or being able to invent and develop one’s own projects within the work context). We describe examples of each from different cultures and offer practical implications of these meanings for the primary stakeholders of career research: individuals, organizations, as well as counselors, coaches and consultants.